Effect of the pollution control measures on PM2.5 during the 2015 China Victory Day Parade: Implication from water-soluble ions and sulfur isotope. (November 2016) - Han, Xiaokun; Guo, Qingjun; Liu, Congqiang; Strauss, Harald; Yang, Junxing; Hu, Jian; Wei, Rongfei; Tian, Liyan; Kong, Jing; Peters, Marc
Abstract: Air pollution by particulate matter is a serious problem in Beijing. Strict pollution control measures have been carried out in Beijing prior to and during the 2015 China Victory Day Parade in order to improve air quality. This distinct event provides an excellent opportunity for investigating the impact of such measures on the chemical properties of particulate matter with an aerodynamic diameter ≤2.5 μm (PM2.5 ). The water-soluble ions as well as sulfur and oxygen isotopes of sulfate in PM2.5 collected between August 19 and September 18, 2015 (n = 31) were analyzed in order to trace the sources and formation processes of PM2.5 in Beijing. The results exhibit a decrease in concentration of water-soluble ions in PM2.5 including aerosol sulfate. In contrast, the mean values of δ 34 Ssulfate (4.7 ± 0.8‰ vs. 5.0 ± 2.0‰) and δ 18 Osulfate (18.3 ± 2.3‰ vs. 17.2 ± 6.0) in PM2.5 during the air pollution control period and the non-source control period exhibit no significant differences, which suggests that despite a reduction in concentration, the sulfate source remains identical for the two periods. It is inferred that the decrease in concentration of sulfate in PM2.5 mainly results from variations in air mass transport. Notably, the air mass during the pollution control period originated mainly from north and northeast and changed to southerly directions thereafter. The sulfur and oxygen isotopes of the sulfate point to coal combustion as the major source of sulfate in PM2.5 from the Beijing area. Graphical abstract: Highlights: Pollution control measures have a significant effect on PM2.5 concentrations. Pollution control measures have only a minor effect on sulfate source of PM2.5. Coal combustion is the major sulfate source for PM2.5 in the Beijing area. Abstract : Air quality improvements recorded during the 2015 Victory Day celebrations resulted from a combination of pollution control measures and meteorological parameters.